Análisis de la inclusión laboral de la mujer afroecuatoriana en las IES de la provincia de Imbabura, período 2017-2018 - Hernández Chapi, Diana Inés (2023)
It is necessary that in Ecuador a detailed study be carried out on the exercise of the rights of Afro-Ecuadorians, particularly women regarding work. The authors acknowledge that the functioning of racism persists throughout the entire Afro Ecuadorian ancestral territory, especially harming women. Hence, the purpose of this research was to determine the current employment situation of Afro-Ecuadorian women in the IES of the Ibarra canton, Imbabura province in the period 2017-2018. Its approach was qualitative and its level of depth was descriptive. In this context, the method used was the legal partner, with the support of the deductive method. This investigation is important because it evidenced the discriminatory situation in the workplace of Afro-Ecuadorian women, which generates inequalities that, without a doubt, contradict the content of the rights provided for in the Constitution and in International Agreements. The Afro people enjoy ownership of twenty-one collective rights, which has repercussions on state and private actors, in various fields, such as labor. In any case, it is concluded that the current employment situation of Afro Ecuadorian women in Ecuador's Higher Education Institutions continues to be precarious, because historical, political, and economic factors still prevail\; therefore, gender gaps and inequities continue to persist, limiting the labor inclusion of these women in the corresponding university institutions.